Knock-down of core proteins regulating microRNA biogenesis has no effect on sensitivity of lung cancer cells to ionizing radiation. - Olga Surova; Nadeem Shahzad Akbar; Boris Zhivotovsky (PLoS ONE, 2012)
Recent studies underline the important role of microRNAs (miRNA) in the development of lung cancer. The main regulators of miRNA biogenesis are the ribonucleases Drosha, Dicer and Ago2. Here the role of core proteins of miRNA biogenesis machinery in the response of human non-small and small cell lung carcinoma cell lines to treatment with ionizing radiation was assessed. We found that Drosha and Dicer were expressed at higher levels in radioresistant but not in sensitive cell lines. However, down-regulation of either Dicer or Drosha had no effect on the sensitivity of cells to irradiation. Elimination of components of the RNA-induced silencing complex Ago2 and Tudor staphylococcal nuclease also did not sensitize cells to the same treatment. Thus, modulation of miRNA biogenesis machinery is not sufficient to increase the radiosensitivity of lung tumors and other strategies are required to combat lung cancer.